2018
DOI: 10.1038/s41433-018-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of ultraviolet radiation in the decrease of corneal endothelial cell density caused by pterygium

Abstract: UV radiation exposure played a significant role in the effect of pterygium decreasing the corneal ECD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
17
2
Order By: Relevance
“…However, the results of our study came to a different conclusion. The ECD decrease in eyes with pterygium from our retrospective study was far less (76 cells/mm 2 , 3.1%) than those in the previous studies [11, 13, 15]. In our retrospective study, the ECD of eyes with unilateral pterygium was almost the same as the ECD of the contralateral eyes.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, the results of our study came to a different conclusion. The ECD decrease in eyes with pterygium from our retrospective study was far less (76 cells/mm 2 , 3.1%) than those in the previous studies [11, 13, 15]. In our retrospective study, the ECD of eyes with unilateral pterygium was almost the same as the ECD of the contralateral eyes.…”
Section: Discussioncontrasting
confidence: 57%
“…In a previous study, outdoor workers with more UV radiation exposure was shown to have lower ECD compared to non-outdoor workers [19]. In a recent study, ECD decrease in eyes with pterygium was also found to be associated with the duration of UV radiation exposure [15]. The other cause of ECD decrease in eyes with pterygium is a variety of pathogenic factors including inflammation, angiogenesis and extracellular matrix modulators [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13, 18 Our retrospective study results demonstrated that the ECD of eyes with unilateral pterygium was almost the same as the ECD of the contralateral normal eyes. Our prospective study showed that ECC hexagonality and ECV in eyes with unilateral PT was also not significantly different from those in the contralateral NPT eyes.…”
mentioning
confidence: 60%
“…Moreover, patients with longer UV exposure had significantly lower overall ECD than patients with short UV exposure. 18 These results suggest that in eyes with pterygium, UV exposure needs to reach a certain threshold to induce ECD decrease. One limitation of our study is that the UV exposure of patients was not recorded.…”
mentioning
confidence: 83%